Kehidupan Sosial Ekonomi Pedagang Di Kawasan Arena Pacu Jalur Kota Teluk Kuantan (2006 - 2022) - Kristina Maharani; Etmi Hardi (Jurusan Sejarah FIS UNP, 2023)
Abstract This study discusses the Socio-Economic Life of Traders in the Kuantan Bay City Racetrack Area (2006-2022). The purpose of this study was to determine the background of the trading community in the area of ​​the runway area, the social and economic life of the merchant community in the area of ​​the runway area of ​​Teluk Kuantan City and to explain the government's role in advancing traders in the area of ​​the runway area of ​​the City of Teluk Kuantan. In this study using the historical method through four stages, namely heuristics, interpretation, and historiography. The results and discussion obtained from this study are (1) Kuantan Singingi Regency has a very well-known tradition, namely the Pacu Balap tradition (2) The Pacu Balap tradition is held every year in order to celebrate the Republic of Indonesia's Independence Day which is carried out on the banks of the Kuantan River (3) The more it is known race track event the government is trying to carry out developments in the area on the edge of the Kuantan River which is named the track runway area (4) The construction of this track runway area, causing capturing business opportunities can affect their socio-economic life, namely by trading. Keywords: Socio-Economic Life, Traders, Racetrack